Morphological Characterization and Topographic Analysis of Multiple Photoreceptor Types in the Retinae of Mesopelagic Hatchetfishes with Tubular Eyes - Biagioni, Lauren M.; Hunt, David M.; Collin, Shaun P. (Frontiers in Ecology and Evolution, 2016)
Marine hatchetfishes, Argyropelecus spp., are one of the 14 genera of mesopelagic teleosts, which possess tubular eyes. The tubular eyes are positioned dorsally on the head and consist of a main retina, which subtends a large dorsal binocular field, and an accessory retina, which subtends the lateral monocular visual field. The topographic distribution of photoreceptors in the retina of Argyropelecus sladeni, A. affinis and A. aculeatus was determined using a random, unbiased and systematic stereological approach, which consistently revealed a region of high density (area centralis) in the central region of the main retina (up to a peak of 96,000 receptors per mm2) and a relatively homogeneous density of photoreceptors in the accessory retina (of approximately 20,000 receptors per mm2). The position of the area centralis in the main retina indicates this retinal region subserves greater spatial resolution in the centre of the dorsal binocular visual field. Light microscopy and transmission electron microscopy also revealed the presence of multiple photoreceptor types (two rod-like and one cone-like) based on the size and shape of the inner and outer segments and ultrastructural differences in the ellipsoidal region. The presence of multiple photoreceptor types in these tubular-eyed, mesopelagic hatchetfishes may reflect the need for the visual system to function under different lighting conditions during vertical migratory behavior, especially given their unique dorsally-facing eyes.